Research trends and hotspots in post-stroke speech rehabilitation: A bibliometric analysis - Nan Huang; Kang Zou; Fang Liu; Zhen Su; Long Chen; Yanbiao Zhong; Yun Luo; Maoyuan Wang; Li Xiao (Acta Psychologica)
Background: With the global population aging, the incidence of stroke is rising, often resulting in motor dysfunction, speech disorders, and swallowing difficulties, significantly affecting daily life and social participation. Speech and language disorders notably impair communication and restrict social engagement, making speech rehabilitation a critical intervention. However, comprehensive bibliometric analyses on post-stroke language rehabilitation are limited, restricting understanding of progress in this field. Objective: This study aimed to identify hotspots and trends in post-stroke speech rehabilitation research from 2003 to 2023 to guide future studies. Methods: Articles on post-stroke speech rehabilitation from 2003 to 2023 were retrieved from the Web of Science Core Collection. Analyses included annual publications, key authors, countries, institutions, journals, co-citations, and keywords. Results: Among 1077 articles, publication volume showed an upward trend, with the United States leading in contributions. The Aphasiology journal published the most articles, and prominent institutions like the University of Queensland demonstrated significant publication and citation impact. Key trends included “communication disorders,” “functional connectivity,” and “melodic intonation therapy,” with “stroke” and “aphasia” emerging as central keywords. Conclusion: Research in post-stroke speech rehabilitation is increasing, with significant contributions from the United States and key institutions. Trends highlight the importance of communication-focused therapies and innovative techniques like melodic intonation therapy. This study provides insights into research directions.